Halal Food Industries Research Halal Food Industries Research (2010–2025): A Bibliometric Analysis of Publication Trends and Scientific Productivity - Magfira Magfira; Ulfa Nurrofingah; Fensa Eka Widjaya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study provides a comprehensive bibliometric analysis of global research on the halal food industry published between 2010 and 2025. Using the Scopus database and bibliometric tools such as Bibliometrix and Biblioshiny, the analysis explores scientific productivity, citation trends, author and institutional impact, and thematic evolution in halal food scholarship. The findings indicate a significant increase in academic output beginning in 2015, with a peak in 2023, reflecting heightened interdisciplinary interest in halal topics beyond religious obligations—spanning food safety, certification, sustainability, consumer trust, and digital innovation. Malaysia and Indonesia emerged as leading contributors, supported by institutional frameworks and national halal agendas. Keyword co-occurrence analysis shows dominant themes such as “halal,” “halal food,” and “halal certification,” alongside emerging areas like blockchain, halal logistics, and ethical consumption. Despite the growing volume and diversity of research, the study identifies underexplored areas, including halal finance, additives, and comparative studies across regions. This analysis contributes to understanding the intellectual structure of halal food research and offers strategic insights for future scholarly exploration and industry development. Keywords: Halal food industry; Bibliometric analysis; Scientific productivity; Halal certification; Research mapping